Educational challenges as experienced by pregnant student nurses at a college in Mpumalang - Khothasane B. Nkosi; Agnes Makhene; Sidwell Matlala (AOSIS, 2019)
Background: Student nurses at a college in Mpumalanga fall pregnant before they complete their training, and some commence training while pregnant and face educational challenges in both theoretical and clinical learning areas. It becomes impossible for them to complete their training on time. Objectives: The objectives of this study were to explore and describe educational challenges as experienced by pregnant student nurses at a college in Mpumalanga and to formulate recommendations that can be used by the college and pregnant student nurses to address their educational challenges. Methods: A qualitative, exploratory, descriptive and contextual research design was used. Ten student nurses were selected through purposive sampling. Data were collected by means of in-depth unstructured individual phenomenological interviews between September and November 2016. Data were analysed using Giorgi's qualitative thematic analysis method. Results: The central theme that emerged from this study confirmed that pregnant student nurses experienced educational challenges negatively. Four main themes that emerged were academic challenges, failure to write examinations, support system and maternity leave. These findings had a negative impact on their education. Conclusion: There is a need for the college to minimise the identified educational challenges to promote completion of training on time.